The Cantareira System, the Largest South American Water Supply System: Management History, Water Crisis, and Learning - Zuffo, Antonio Carlos; Duarte, Sergio Nascimento [UNESP]; Jacomazzi, Marco Antonio; Cucio, Maíra Simões; Galbetti, Marcus Vinícius (MDPI, 2023)
Located in the southeast region of Brazil, the Cantareira System consists of six interconnected reservoirs and supplies around 14 million people in the state of São Paulo. Built in the 1970s, when extensive fluviometric series were not available in the region, the system underwent several operating rules that culminated in the water crisis caused by the 2014/2015 drought. This article makes a brief critical account of what has been experienced in these almost 50 years of operating the system, the factors that influenced the water crisis, and what has been learned.
Keywords: Cantareira System; drought; reservoirs